2005
DOI: 10.1258/0022215054352171
|View full text |Cite
|
Sign up to set email alerts
|

Triple-layer laryngeal closure for intractable aspiration

Abstract: Impaired laryngeal protective function can result in intractable aspiration, which causes recurrent life-threatening pneumonia. Several surgical operations have been developed to treat intractable aspiration. In this case, we report a successful case of triple-layer laryngeal closure, which was performed in a patient with type II diabetes mellitus and nutritional failure due to intractable aspiration that had been caused by several stroke attacks. Triple-layer laryngeal closure is a unique modified technique t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…For patients with intractable aspiration who have no chance of recovery of laryngeal function surgical procedures should be definitive as laryngotracheal separation or tracheoesophageal diversion, total laryngectomy, supraglottic closure, glottic closure and triple-layer laryngeal closure [2,3]. Literature review has revealed that the supraglottic closure is also associated with a high failure rate [4].…”
Section: To the Editormentioning
confidence: 99%
“…For patients with intractable aspiration who have no chance of recovery of laryngeal function surgical procedures should be definitive as laryngotracheal separation or tracheoesophageal diversion, total laryngectomy, supraglottic closure, glottic closure and triple-layer laryngeal closure [2,3]. Literature review has revealed that the supraglottic closure is also associated with a high failure rate [4].…”
Section: To the Editormentioning
confidence: 99%
“…[ 9 ] Therefore, the damping performance of laminates can be optimized by inserting damping layers into the variable angle laminates. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, surgeries to prevent entry of material into the airway should achieve seven goals: 1) Protection of the airway from soilage, 2) allow safe swallowing, 3) allow unimpeded respiration, 4) be simple to perform,5) have a minimum risk of complications, 6) allow phonation, and 7) to be potentially reversible 3, 11–14. The latter two goals are primarily based on the fact that many of these techniques were developed for adults who are impaired after a major head and neck resection or cerebrovascular accident.…”
Section: Introductionmentioning
confidence: 99%